2012
DOI: 10.1021/la205084z
|View full text |Cite
|
Sign up to set email alerts
|

Silk–Silica Composites from Genetically Engineered Chimeric Proteins: Materials Properties Correlate with Silica Condensation Rate and Colloidal Stability of the Proteins in Aqueous Solution

Abstract: The aim of the study was to determine the extent and mechanism of influence on silica condensation that is presented by a range of known silicifying recombinant chimeras (R5- SSKKSGSYSGSKGSKRRIL; A1- SGSKGSKRRIL; and Si4-1- MSPHPHPRHHHT and repeats thereof) attached at the N-terminus end of a 15 mer repeat of the 32 amino acid consensus sequence of the major ampullate dragline Spindroin 1 (Masp1) Nephila clavipes spider silk sequence ([SGRGGLGGQG AGAAAAAGGA GQGGYGGLGSQG]15X). The influence of the silk/chimera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 40 publications
2
44
0
Order By: Relevance
“…The silicification reactions were performed according to our prior methods [1,21]. The lyophilized 6mer and chimera proteins were dissolved in double distilled water and then filtered with 5.0 μm syringe filters (Millipore, MA) to remove insoluble precipitates.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The silicification reactions were performed according to our prior methods [1,21]. The lyophilized 6mer and chimera proteins were dissolved in double distilled water and then filtered with 5.0 μm syringe filters (Millipore, MA) to remove insoluble precipitates.…”
Section: Methodsmentioning
confidence: 99%
“…The process of silica precipitation in solution at pH 7.0 was monitored by turbidity at 595 nm [1] with a plate reader Spectra-Max M2 (Molecular Device, CA) from three independent experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[173] It has been long demonstrated that encapsulation mediated by fusion proteins endowed with silica-forming activity increases entrapment efficiency. [173,174,37,[175][176][177][178][179][180][181][182] We have thus investigated the outcome -in terms of spectral quality, entrapment efficiency, catalytic activity and spectroscopic properties of the matrix -of fusing the R5 peptide to our target enzyme [183].…”
Section: Protein Nmr Studiesmentioning
confidence: 99%